Economic Impact of ECDIS Implementation on Maritime Logistics and Insurance Costs: A PLS-SEM Analysis of Indonesian Fertilizer Distribution - Sumiyatiningsih; Agung Kwartama; Didik Indriawan; Ramayanti; Lie Adek (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
This study evaluates the operational and economic impacts of implementing the Electronic Chart Display and Information System (ECDIS) across the maritime distribution of fertilizers and seeds. Using the commercial vessel MV Caraka 123 as a representative macro-model for Indonesian archipelagic logistics, the research directly addresses a critical gap. While the technical safety advantages of ECDIS are widely acknowledged, empirical evidence quantifying its actual financial return on investment remains severely limited. A quantitative approach utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed. The study analyzed perceptual survey data from 200 active maritime personnel integrated alongside objective, ratio-scale ship logs. The results decisively indicate that optimal ECDIS implementation heavily drives logistics cost efficiency (β = 0.815, p < 0.001). This efficiency manifests primarily through substantial, verifiable reductions in fuel consumption and voyage time a direct result of highly accurate route planning and real-time environmental monitoring. Furthermore, the findings demonstrate that the objective navigational safety records generated by ECDIS provide ship operators with a robust, data-backed foundation for negotiating lower marine insurance premiums by demonstrably mitigating claim risks. Ultimately, the structural model confirms that ECDIS digitalization acts not merely as a regulatory safety requirement, but as a strategic financial investment delivering tangible savings in both operational and risk-management expenditures.